Pregnant Women with Normal Birth Babies - Nuke Devi Indrawati; Maria Ulfah Kurnia Dewi; Dian Nintyasari Mustika; Dewi Puspitaningrum; Sherkia Ichtiarsi Prakasiwi; Azizatus Sabila; Sri Rahayu (GLOBAL HEALTH SCIENCE GROUP, 2022)
Anemia is one of the most common complications during pregnancy. Normal physiological changes during pregnancy affect hemoglobin (Hb), and there is a relative or absolute reduction in Hb concentration. The most common anemia during pregnancy are iron deficiency anemia (about 75%) and folate deficiency megaloblastic anemia, which especially in women during pregnancy do not receive adequate and appropriate prenatal iron and folate supplements. Research aims to find out the rusteristic picture of pregnant women who have anemia. Study design Cohort Retrospective, purposive sampling technique. The recipe numbers 50. The results of the study of respondents aged 20-35 years as many as 41 respondents (82%), Secondary respondent education category as many as 27 respondents (54%), IRT respondent job category as many as 34 respondents (68%), Hb TM I categories respondents are not anemic as many as 31 respondents (62%). Category Hb TM II Mild anemia as many as 30 respondents (60%), hb TM III category is normal as many as 35 respondents (70%). The conclusion that improved services during pregnancy examinations need to be done continuously and correctly for example in doing hb examinations, monitoring the weight gain of women during pregnancy, and other supporting examinations. More research is needed on the application of maternal and newborn health science technology innovations.